Event-triggered output feedback control for distributed networked systems. (January 2016) - Mahmoud, Magdi S.; Sabih, Muhammad; Elshafei, Moustafa
Abstract: This paper addresses the problem of output-feedback communication and control with event-triggered framework in the context of distributed networked control systems. The design problem of the event-triggered output-feedback control is proposed as a linear matrix inequality (LMI) feasibility problem. The scheme is developed for the distributed system where only partial states are available. In this scheme, a subsystem uses local observers and share its information to its neighbors only when the subsystem׳s local error exceeds a specified threshold. The developed method is illustrated by using a coupled cart example from the literature. Abstract : Highlights: In this paper, we have provided a solution to the problem of event-triggered output-feedback control within the framework of distributed networked control systems. A major feature of the output-based controller is that the design is based on the local observed dynamics and the information shared by neighboring interacting subsystems. The control law is designed in two parts to take care of individual dynamics as well as the coupling of the subsystems. The proposed design is illustrated by using a benchmark example of a batch reactor which shows the stabilizing results of the control system.